Preparation method of fine-grain near-alpha high-temperature titanium alloy
By adjusting SLM processing parameters and combining heat treatment processes, optimizing the structural structure of high-temperature titanium alloys, the problems of coarse grains and uneven structure in additive manufacturing are solved, and the mechanical and thermal properties of the materials are significantly improved.
Patent Information
- Application Number
- CN202510287463.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The existing high-temperature titanium alloys are prone to form coarse grains and uneven net basket structure during the additive manufacturing process, which affects the comprehensive performance of the material. It is difficult for traditional heat treatment processes to eliminate rapid solidification structure and residual stress.
Optimize the internal structure of the titanium alloy by adjusting SLM processing parameters such as laser power, scanning speed and scanning spacing, combined with stress treatment, solution treatment and aging treatment processes.
The density, mechanical properties, thermal stability and creep resistance of the alloy material are significantly improved, and the possibility of performance degradation caused by surface oxidation is reduced.
Smart Images

Figure CN119800138A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a method for preparing a fine-grained near-alpha high-temperature titanium alloy. Background Art
[0002] With the rapid development of the aerospace industry, the performance requirements for related metals and alloy materials are getting higher and higher. Among them, titanium alloys resistant to high temperatures of 600°C have become ideal materials for manufacturing components such as blades and blisks of aircraft engines and spacecraft due to their excellent specific strength, corrosion resistance and high temperature resistance. The basketweave structure in high-temperature titanium alloys is composed of needle-shaped α phase and β phase. The structure of the basketweave structure shows higher strength than other structures when deformed at 800~900°C. This is because the more fine needle-shaped α phase grain boundaries in the basketweave structure become obstacles to the movement of movable dislocations, and the strength of the material can be maintained even at high temperatures. The grains are relatively uniform spherical or polyhedral in shape, with significant orientation distribution and comparable grain size. They have excellent plasticity and toughness, and exhibit excellent high-temperature mechanical properties and low temperature sensitivity. In addition, the flow stress of the basketweave structure is basically unaffected by temperature when deformed at around 600°C, showing good thermal stability. These characteristics give the basketweave structure significant application advantages in high-temperature titanium alloys, especially in the manufacture of components with high requirements for high-temperature performance of materials in fields such as aerospace.
[0003] Traditional casting and forging processes have many limiting factors when manufacturing high-temperature titanium alloy parts with complex shapes, such as high equipment cost, low material utilization rate, and long manufacturing cycle. Selective laser melting (SLM technology), as an emerging additive manufacturing technology, can accurately control the accumulation of materials, manufacture parts with complex shapes, and has high material utilization rate and short manufacturing cycle. However, the application of high-temperature titanium alloy Ti60 additive manufacturing of large components at 600°C is still in the exploratory stage. It is easy to form a strong texture during the printing process, making the grains coarse, affecting the comprehensive performance of the material; at the same time, traditional alloy heat treatment processes are often difficult to fully eliminate the rapid solidification structure and residual stress generated during additive manufacturing, and are prone to form Widmanstatten structure, which makes the basket structure uniformity poor, further limiting the improvement of alloy performance. Therefore, it is necessary to optimize and explore the forming and heat treatment processes of alloy materials. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a fine-grained near-α high-temperature titanium alloy in order to solve the above technical problems. By controlling the internal structure of the titanium alloy through appropriate SLM processing parameters and heat treatment process, an alloy material with good mechanical properties is obtained.
[0005] The method for preparing a fine-grained near-α high-temperature titanium alloy in the technical solution of the present invention comprises the following steps: (1) Filling alloy powder onto a building platform of an SLM processing device and starting SLM processing; during SLM processing, the laser power is 260-380 W, the scanning speed is 1000-1500 mm / s, and the scanning spacing is 0.05-0.15 mm; the alloy powder is a mixture of Ti60 alloy powder, boron powder, and iron powder; (2) The product obtained by SLM processing is subjected to stress relief treatment, solution treatment and aging treatment in sequence; the temperatures of stress relief treatment and aging treatment are independently selected from 600~1000℃, the temperature of solution treatment is 1000~1300℃, and the temperature of solution treatment is greater than the temperature of stress relief treatment and the temperature of aging treatment.
[0006] By adjusting the laser power, scanning speed and scanning spacing, cracks and pore defects in the forming process are avoided, good metallurgical bonding between each layer of melt and between layers is ensured, and the density of the alloy material is significantly improved, thereby improving the mechanical properties of the material and enhancing its application potential in harsh environments. Stress relief heat treatment can eliminate the residual stress generated during the manufacturing process, solid solution treatment can fully dissolve the strengthening phase in the alloy and eliminate the rapid solidification structure, and aging treatment can promote the nucleation and growth of the precipitated phase. The three are carried out in sequence to optimize the microstructure and obtain a uniform basket structure, which significantly improves the strength-plasticity matching, thermal stability and creep resistance of the alloy, and reduces the possibility of performance degradation due to surface oxidation.
[0007] Furthermore, the chemical composition of the Ti60 alloy powder consists of the following components in mass percentage: Al 5.2~6.0%, Mo 0.2~1.0%, Sn 3.0~4.5%, Zr 2.5~4.0%, Si 0.2~ 0.6%, Ta 0.2~1.5%, Nb 0.2~0.7%, C 0.02~0.08%, and the balance is Ti.
[0008] Preferably, the Ti60 alloy powder is pre-dried at 60-100° C. for 6-12 hours to remove moisture, and a screening device is used to remove impurities and large particles in the alloy powder.
[0009] Preferably, the particle size of the Ti60 alloy powder is 15-60 μm.
[0010] Furthermore, the mass of boron powder and iron powder is 0.005-0.02% of the mass of Ti60 alloy powder. Adding trace amounts of boron powder and iron powder to Ti60 alloy powder and introducing B and Fe elements can provide heterogeneous nucleation points, promote grain refinement, reduce the formation of columnar grains, help reduce the anisotropy of alloy materials, and improve their uniform performance in different directions, which is crucial to improving the overall performance and reliability of components.
[0011] Furthermore, in step (1), the laser power during SLM processing is 280-350 W, the scanning speed is 1200-1400 mm / s, and the scanning spacing is 0.09-0.11 mm. Reasonable laser power, scanning speed, and scanning spacing can reduce the formation of texture, significantly refine the grains, help reduce the anisotropy of the material, improve its uniform performance in different directions, and improve the overall performance and reliability of the component.
[0012] Furthermore, in step (1), the thickness of the alloy powder filled onto the building platform of the SLM processing equipment is 30-60 μm.
[0013] Furthermore, in step (2), the temperature of the stress relief treatment is 700-900°C, and the time is 1-5 hours; the temperature of the solution treatment is 1000-1200°C, and the time is 1-5 hours; the temperature of the aging treatment is 600-800°C, and the time is 1-10 hours.
[0014] Furthermore, in step (2), the temperature of the solution treatment minus the temperature of the stress relief treatment is ≤ 200° C. By controlling the temperature of the heat treatment, it is possible to avoid the internal residual tensile stress exceeding the alloy strength due to excessive temperature gradient, thereby effectively controlling the generation of cracks.
[0015] The present invention also provides a fine-grained near-α high-temperature titanium alloy, which is prepared by the above-mentioned preparation method of the fine-grained near-α high-temperature titanium alloy.
[0016] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: (1) By adjusting and controlling the laser power, scanning speed and scanning spacing during the SLM processing, combined with a reasonable and effective heat treatment process, an alloy material with a density better than 99.95% was obtained, which significantly improved its mechanical properties, thermal stability and creep resistance. (2) Adding trace amounts of B and Fe elements to Ti60 alloy powder can provide heterogeneous nucleation sites, promote grain refinement, reduce the formation of columnar grains, help reduce the anisotropy of the alloy material, and improve its uniform performance in different directions, which is crucial to improving the overall performance and reliability of the components; (3) Through reasonable SLM processing technology, the formation of texture can be reduced, the grain size can be significantly refined, which helps to reduce the anisotropy of the material, avoid cracks and pore defects during the forming process, ensure good metallurgical bonding between each layer of melt and between layers, and significantly improve the density of the alloy material, thereby improving the mechanical properties of the material and enhancing its application potential in harsh environments; (4) Combining stress relief heat treatment, solution treatment and aging treatment can optimize the microstructure and obtain a uniform basketweave structure, significantly improve the strength-plasticity matching, thermal stability and creep resistance of the alloy, and reduce the possibility of performance degradation due to surface oxidation; (5) By adjusting the temperature of stress relief heat treatment, solution treatment and aging treatment, the internal residual tensile stress exceeding the alloy strength due to excessive temperature gradient can be avoided, thereby effectively controlling the occurrence of cracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a microstructure photograph of the fine-grained near-α high-temperature titanium alloy obtained in Example 1; Figure 2 This is a microstructure photograph of the fine-grained near-α high-temperature titanium alloy obtained in Example 2. DETAILED DESCRIPTION
[0018] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0019] The Ti60 alloy powder provided by Asia New Materials Co., Ltd. used in the following examples and comparative examples consists of the following components in percentage by mass: Al 5.5%, Mo 0.7%, Sn 3.7%, Zr 3.2%, Si 0.4%, Ta 1.1%, Nb 0.5%, C 0.05%, and the balance is Ti. Example 1
[0020] The preparation method of the fine-grained near-α high-temperature titanium alloy of this embodiment comprises the following steps: (1) Ti60 alloy powder was dried at 80°C for 8 h to remove moisture, and then impurities and large particles in the powder were removed using screening equipment; (2) The sieved titanium alloy powder was evenly mixed with 0.01% boron powder and 0.01% iron powder, and filled onto the construction platform of the SLM processing equipment with a layer thickness of 50 μm. The laser power was adjusted to 340 W, the scanning speed was set to 1350 mm / s, the scanning pitch was 0.09 mm, the laser spot size was 90 m, the scanning rotation angle was 67°, the shape and energy distribution of the molten pool were controlled, and the SLM processing was started; (3) The products obtained by SLM processing were subjected to stress relief treatment, solution treatment and aging treatment in sequence. The stress relief treatment was carried out at 850℃ for 2h, the solution treatment was carried out at 1035℃ for 2h, and the aging treatment was carried out at 700℃ for 5h. The microstructure of the obtained fine-grained near-α high-temperature titanium alloy is as follows: Figure 1 As shown, a large number of elongated α phases can be seen, some of which are arranged regularly. Example 2
[0021] The preparation method of the fine-grained near-α high-temperature titanium alloy of this embodiment comprises the following steps: (1) The titanium alloy powder was dried at 80°C for 8 hours to remove moisture, and then the impurities and large particles in the powder were removed using screening equipment; (2) The sieved titanium alloy powder, 0.015% by weight of boron powder, and 0.01% by weight of iron powder were uniformly mixed and filled onto the construction platform of the SLM processing equipment with a layer thickness of 50 μm. The laser power was adjusted to 360 W, the scanning speed was set to 1360 mm / s, the scanning pitch was 0.10 mm, the laser spot size was 90 m, the scanning rotation angle was 67°, the shape and energy distribution of the molten pool were controlled, and the SLM processing was started; (3) The products obtained by SLM processing were subjected to stress relief treatment, solution treatment and aging treatment in sequence. The stress relief treatment was carried out at 900℃ for 2h, the solution treatment was carried out at 1050℃ for 2h, and the aging treatment was carried out at 750℃ for 5h. The microstructure of the obtained fine-grained near-α high-temperature titanium alloy is as follows: Figure 2 As shown, a large number of elongated α phases can be seen, some of which are arranged regularly. Example 3
[0022] The preparation method of the fine-grained near-α high-temperature titanium alloy of this embodiment comprises the following steps: (1) The titanium alloy powder was dried at 80°C for 8 hours to remove moisture, and then the impurities and large particles in the powder were removed using screening equipment; (2) The sieved titanium alloy powder was evenly mixed with 0.01% boron powder and 0.015% iron powder, and filled onto the construction platform of the SLM processing equipment with a layer thickness of 50 μm. The laser power was adjusted to 350 W, the scanning speed was set to 1300 mm / s, the scanning pitch was 0.11 mm, the laser spot size was 90 m, the scanning rotation angle was 67°, the shape and energy distribution of the molten pool were controlled, and the SLM processing was started; (3) The products obtained by SLM processing were subjected to stress relief treatment, solution treatment and aging treatment in sequence. The stress relief treatment was carried out at 930°C for 2 h, the solution treatment was carried out at 1050°C for 2 h, and the aging treatment was carried out at 800°C for 5 h. Example 4
[0023] The difference between this embodiment and embodiment 1 is that in step (2), the sieved titanium alloy powder and 0.01% by mass of boron powder are mixed evenly, and filled onto the building platform of the SLM processing equipment with a layer thickness of 50 μm, the laser power is adjusted to 355 W, the scanning speed is set to 1350 mm / s, the scanning pitch is 0.09 mm, the laser spot size is 90 m, the scanning rotation angle is 67°, the shape of the molten pool and the energy distribution are controlled, and the SLM processing is started. Example 5
[0024] The difference between this embodiment and embodiment 1 is that in step (2), the sieved titanium alloy powder and 0.01% by weight of iron powder are mixed evenly, and filled onto the building platform of the SLM processing equipment with a layer thickness of 50 μm, the laser power is adjusted to 355 W, the scanning speed is set to 1350 mm / s, the scanning pitch is 0.09 mm, the laser spot size is 90 m, the scanning rotation angle is 0°, the shape of the molten pool and the energy distribution are controlled, and the SLM processing is started. Example 6
[0025] The difference between this embodiment and embodiment 1 is that in step (2), the sieved titanium alloy powder, 0.01% by mass of boron powder and 0.05% by mass of iron powder are evenly mixed, and filled onto the building platform of the SLM processing equipment with a layer thickness of 50 μm, the laser power is adjusted to 355 W, the scanning speed is set to 1350 mm / s, the scanning pitch is 0.09 mm, the laser spot size is 90 m, the scanning rotation angle is 67°, the shape of the molten pool and the energy distribution are controlled, and the SLM processing is started. Example 7
[0026] The difference between this embodiment and embodiment 1 is that in step (2), the sieved titanium alloy powder, 0.50% by mass of boron powder and 0.01% by mass of iron powder are evenly mixed, and filled onto the building platform of the SLM processing equipment with a layer thickness of 50 μm, the laser power is adjusted to 355 W, the scanning speed is set to 1350 mm / s, the scanning pitch is 0.09 mm, the laser spot size is 90 m, the scanning rotation angle is 67°, the shape of the molten pool and the energy distribution are controlled, and the SLM processing is started. Example 8
[0027] The difference between this embodiment and embodiment 1 is that in step (3), the product obtained by SLM processing is subjected to stress relief treatment, solution treatment and aging treatment in sequence, the stress relief treatment is carried out at 800°C for 2 hours, the solution treatment is carried out at 1100°C for 2 hours, and the aging treatment is carried out at 700°C for 5 hours. Comparative Example 1
[0028] The difference between this comparative example and Example 1 is that in step (2), the sieved titanium alloy powder and 0.01% by mass of boron powder and 0.01% by mass of iron powder are uniformly mixed, and filled onto the building platform of the SLM processing equipment with a layer thickness of 50 μm, the laser power is adjusted to 200 W, the scanning speed is set to 800 mm / s, the scanning pitch is 0.09 mm, the laser spot size is 90 m, the scanning rotation angle is 0°, the shape and energy distribution of the molten pool are controlled, and the SLM processing is started. Comparative Example 2
[0029] The difference between this comparative example and Example 1 is that in step (2), the sieved titanium alloy powder and 0.01% by weight of boron powder and 0.01% by weight of iron powder are uniformly mixed, and filled onto the building platform of the SLM processing equipment with a layer thickness of 50 μm, the laser power is adjusted to 400 W, the scanning speed is set to 1600 mm / s, the scanning pitch is 0.09 mm, the laser spot size is 90 m, the scanning rotation angle is 0°, the shape and energy distribution of the molten pool are controlled, and the SLM processing is started. Comparative Example 3
[0030] The difference between this comparative example and Example 1 is that (2) the titanium alloy powder obtained by screening is filled onto the building platform of the SLM processing equipment with a layer thickness of 50 μm, the laser power is adjusted to 355 W, the scanning speed is set to 1350 mm / s, the scanning pitch is 0.09 mm, the laser spot size is 90 m, the scanning rotation angle is 67°, the shape of the molten pool and the energy distribution are controlled, and the SLM processing is started. Comparative Example 4
[0031] The difference between this comparative example and Example 1 is that in step (3), the product obtained by SLM processing is subjected to stress relief treatment and solution treatment in sequence, the stress relief treatment is carried out by keeping the temperature at 850°C for 2 hours, and the solution treatment is carried out by keeping the temperature at 1035°C for 2 hours. Comparative Example 5
[0032] The difference between this comparative example and Example 1 is that in step (3), the product obtained by SLM processing is subjected to stress relief treatment and aging treatment in sequence, the stress relief treatment is carried out by keeping the temperature at 850°C for 2 hours, and the aging treatment is carried out by keeping the temperature at 700°C for 5 hours. Comparative Example 6
[0033] The difference between this comparative example and Example 1 is that in step (3), the product obtained by SLM processing is subjected to solution treatment and aging treatment in sequence, the solution treatment is carried out at 1035°C for 2 hours, and the aging treatment is carried out at 700°C for 5 hours.
[0034] The mechanical properties and creep resistance of the titanium alloys obtained in the above embodiments and comparative examples were tested. The high-temperature tensile strength and high-temperature elongation were tested at 600°C, and the creep deformation was evaluated under the conditions of 600°C / 400MPa / 30min (refer to GB / T 2039). The test results are shown in Table 1.
[0035] Table 1 Titanium alloy performance data table .
[0036] In Examples 1-3, an alloy material with a density higher than 99.80% is obtained by suitable SLM processing parameters and an effective heat treatment process, showing excellent mechanical properties, thermal stability and creep resistance; in Example 4, the alloy powder comprises titanium alloy powder and boron powder, without adding iron powder, and in Example 5, the alloy powder comprises titanium alloy powder and iron powder, without adding boron powder, the effect of grain refinement is poor, the uniformity of the alloy material is low, and the mechanical properties are poor; in Example 6, 0.01% boron powder by mass and 0.05% iron powder by mass of the titanium alloy powder are added, and in Example 7, 0.50% boron powder by mass and 0.01% iron powder by mass of the titanium alloy powder are added, and the dispersion uniformity in the alloy material system is reduced, resulting in low uniformity of the internal components of the alloy material, and poor mechanical properties and creep resistance; in Example 8, the temperature of the solution treatment is quite different from the temperature of the stress relief treatment, and the internal residual tensile stress is large, which makes the performance of the alloy material poor; in Comparative Example 1, the stress relief during SLM processing is very large. The light power and scanning speed are small, the energy density of the alloy material becomes smaller, the density is reduced, and the performance of the alloy material deteriorates; in Example 2, the laser power and scanning speed during SLM processing are large, the energy density is low, the material porosity is large, and the mechanical properties are poor; in Example 3, only titanium alloy powder is used for SLM processing, and iron powder and boron powder are not added, the grain refinement effect is poor, the uniformity of the alloy material is low, the degree of anisotropy is increased, and the mechanical properties deteriorate; in Example 4, only stress relief treatment and solid solution treatment are performed, and no aging treatment is performed, which is not conducive to the further nucleation and growth of alloy crystals, and the performance of the obtained titanium alloy deteriorates; in Example 5, only stress relief treatment and aging treatment are performed, and no solid solution treatment is performed. The internal phase distribution of the alloy material is uneven, and the organizational structure has different phases, which makes the performance of the obtained titanium alloy deteriorate; in Example 6, only solid solution treatment and aging treatment are performed, and no stress relief treatment is performed, and the residual stress generated in the manufacturing process cannot be effectively eliminated, so that the alloy has excessive internal stress, causing a decline in performance.
[0037] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A method for preparing a fine-grained near-α high-temperature titanium alloy, characterized in that: The following steps are involved: (1) Filling alloy powder onto a building platform of an SLM processing device and starting SLM processing; during SLM processing, the laser power is 260-380 W, the scanning speed is 1000-1500 mm / s, and the scanning spacing is 0.05-0.15 mm; the alloy powder is a mixture of Ti60 alloy powder, boron powder, and iron powder; (2) The product obtained by SLM processing is subjected to stress relief treatment, solution treatment and aging treatment in sequence; the temperatures of stress relief treatment and aging treatment are independently selected from 600~1000℃, the temperature of solution treatment is 1000~1300℃, and the temperature of solution treatment is greater than the temperature of stress relief treatment and the temperature of aging treatment.
2. The preparation method according to claim 1, characterized in that: The chemical composition of the Ti60 alloy powder consists of the following components in mass percentage: Al 5.2~6.0%, Mo 0.2~1.0%, Sn 3.0~4.5%, Zr 2.5~4.0%, Si 0.2~0.6%, Ta 0.2~1.5%, Nb 0.2~0.7%, C 0.02~0.08%, and the balance is Ti.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of Ti60 alloy powder is 15~60μm.
4. The preparation method according to claim 1, characterized in that: The mass of boron powder and iron powder is 0.005~0.02% of the mass of Ti60 alloy powder.
5. The preparation method according to claim 1, characterized in that: In step (1), during SLM processing, the laser power is 280-350 W, the scanning speed is 1200-1400 mm / s, and the scanning spacing is 0.09-0.11 mm.
6. The preparation method according to claim 1, characterized in that: In step (1), the thickness of the alloy powder filled onto the building platform of the SLM processing equipment is 30-60 μm.
7. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the stress relief treatment is 700-900°C, and the time is 1-5 hours; the temperature of the solution treatment is 1000-1200°C, and the time is 1-5 hours; the temperature of the aging treatment is 600-800°C, and the time is 1-10 hours.
8. The preparation method according to claim 7, characterized in that: The temperature of the solution treatment in step (2) - the temperature of the stress relief treatment is ≤ 200°C.
9. A fine-grained near-alpha high-temperature titanium alloy, characterized in that: The method is prepared according to claim 1.
Citation Information
Patent Citations
Improvement method for titanium alloy laser 3D printing
CN104928513A
Titanium-based alloy and method for manufacturing a titanium-based alloy component by an additive manufacturing process
CN109680183A
Method for manufacturing high-strength titanium alloy containing segregation-prone elements through 3D printing
CN115740500A
Preparation process method of TA15 titanium alloy with long fatigue life based on selective laser melting forming
CN115846682A
Near-alpha high-temperature titanium alloy with use temperature of 680 DEG C and preparation method
CN116949317A
Cited By
Titanium alloy powder for selective laser melting, preparation method and application
CN120350268A
Titanium alloy powder for laser selective melting, preparation method and application
CN120350268B
Laser powder bed molten high-plasticity TC4 titanium alloy and preparation method and application thereof
CN122057927A
Laser powder bed melting high plasticity TC4 titanium alloy and preparation method and application thereof
CN122057927B